2010
DOI: 10.52321/geolbalc.39.3.3
|View full text |Cite
|
Sign up to set email alerts
|

40Ar/39Ar and U-Pb geochronology of the Iran Tepe volcanic complex, Eastern Rhodopes

Abstract: The Iran Tepe volcanic complex occurs in the south-eastern part of the Eastern Rhodope massif. The rocks are represented by calc-alkaline and high-K calc-alkaline basaltic andesite to dacite epiclastics, lava flows and dikes, which are crosscut by andesitic and latitic dikes and rhyolitic dykes from the Planinets dyke swarm. Stratigraphic data and existing K/Ar ages suggest that the Iran Tepe volcanic complex is Upper Eocene (35-39 Ma), and is one of the oldest volcanic structures in the Eastern Rhodopes. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Lately, it has been suggested that the Eastern Rhodope gold deposits have been related to intrusions of deepseated mafic magmas [61]. The first author of the present study thinks that such mafic rocks should be parental of both epithermal mineralization and Iran Tepe volcano since the volcanic rocks of the latter bear calc-alkaline and high-K characteristics [34]. The second possibility exists because of the presence of old intrusive rocks of similar high-K characteristics in depth.…”
Section: Possible Sources Of Tementioning
confidence: 61%
See 1 more Smart Citation
“…Lately, it has been suggested that the Eastern Rhodope gold deposits have been related to intrusions of deepseated mafic magmas [61]. The first author of the present study thinks that such mafic rocks should be parental of both epithermal mineralization and Iran Tepe volcano since the volcanic rocks of the latter bear calc-alkaline and high-K characteristics [34]. The second possibility exists because of the presence of old intrusive rocks of similar high-K characteristics in depth.…”
Section: Possible Sources Of Tementioning
confidence: 61%
“…For the Krumovgrad goldfield the relationship between precious metal mineralizationmagmatism remains unclear. The goldfield is older (35 ± 0.2 Ma Ar/Ar age of adularia) [9]) than the near-by Iran Tepe volcano (~33.9 Ma for the oldest lava flow) [34] which is the oldest Tertiary volcano in the Eastern Rhodope Mountain [35,36]. That still maintains a question about the origin of the Krumovgrad goldfield.…”
mentioning
confidence: 99%
“…The voluminous late Eocene-Oligocene postcollisional volcanism in the Eastern Rhodope area of South Bulgaria was initially identified to span 37-25.5 Ma by K-Ar ages of numerous paleovolcanoes (Lilov et al, 1987). Subsequently, the timing of volcanism was refined by 40 Ar/ 39 Ar ages to spread essentially in the early Oligocene between 34.62±0.46 Ma and 31.13±0.12 Ma (e.g., Marchev et al, 2010). In the Thrace area of Northern Greece, the temporal spread of the Oligocene volcanism is bracketed between 33.5 Ma and 25.4 Ma as derived from K-Ar ages (Christofides et al, 2004).…”
Section: Geological Settingmentioning
confidence: 99%
“…The Thrace basin represents a wide syn-and posttectonic depression exposed on the territories of Bulgaria, Greece and Turkey, which is filled by different facies and composition Eocene to Quaternary sedimentary successions reaching a thickness of up to 9 km (Kopp, 1961;Siyako et al, 1989;Okay et al, 1991;Boyanov and Goranov, 2001). Upper Eocene (Priabonian) and Oligocene carbonate sedimentary sections in this basin contain reef buildups, whose construction predates or is coeval with the voluminous post-collisional Oligocene volcanism (Harkovska et al, 1989;Christofides et al, 2004;Marchev et al, 2010) in the Eastern Rhodope-Thrace region (Fig. 1).…”
Section: Introductionmentioning
confidence: 97%